Comparison of excision and primary closure vs. crystallized phenol treatment in pilonidal sinus disease: A comparative retrospective study - Turhan, Veysel Barış; Ünsal, Abdulkadir; Öztürk, Doğan; Öztürk, Bülent; Buluş, Hakan (Journal of Surgery and Medicine, 2021)
Background/Aim: Pilonidal sinus is an inflammatory condition that affects the intergluteal sulcus. Since there is no standard treatment for pilonidal sinus, comparative studies are needed. Our study aimed to comparatively evaluate the treatment success, postoperative complications and recurrence in excision/primary repair surgery and crystallized phenol application in pilonidal sinus disease. Methods: A total of 376 pilonidal sinus patients over the age of 18 years who visited our general surgery clinic between January 2017-January 2020 were included in this retrospective cohort study. They were divided into two groups based on whether they underwent phenol treatment or surgery. The patients’ age, body mass index (BMI), gender, number of pits, length of stay in the hospital, return to normal life, mean follow-up times, complications, and satisfaction data were recorded. At the end of the follow-up period, all patients were contacted by telephone and the recurrence rates were noted. Results: Both groups were similar in terms of age, gender, and BMI (P>0.05 for all). The mean age of 374 patients included in the study was 23.38 (4.9) years. The mean follow-up time was 25.47 months. Patients in the crystallized phenol group did not require hospitalization. In the primary repair group, the median length of hospital stay was 1.15 days. Complications such as wound infection, hematoma, and wound dehiscence were significantly less in the phenol group. The recurrence rates in the phenol and primary repair groups were 8% and 10%, respectively (P=0.326). Return to normal life was significantly faster in the phenol group. The success rate in the phenol group was 92%. Conclusion: Although the recurrence rates are similar, crystallized phenol therapy is superior to primary repair due to better wound healing rates, ease of application, and fewer complication rates. More than one application is recommended in phenol treatment.